Dictionary of Abstract the Words of the Russian Language: Nouns with High Numerical Measure of Abstractness - Volskaya, Yulia Aleksandrovna; Zhuravkina, Irina Sergeevna; Lobanov, Alexander Pavlovich (International Journal of Criminology and Sociology, 2022)
This article demonstrates an experiment based on one of the possible means of creating a semantic dictionary of abstract words. It also analyzes its first results, lexical units that have shown a high level of abstraction in our enquiry among native speakers. The widening field of researches that study abstract words demands a precise definition of units that can be classified as concrete nouns as opposed to the abstract ones. However, this task is made more difficult by a polysemy and complex semantic structure of abstract words. Ideas of cognitive approach point to the fact that one word can have features of both concrete and abstract units, to a different extent depending on context and individual perception. In this approach, the leading role belongs to the semantic criterion of differentiating between concrete and abstract lexical units. It is suggested that this principle should be taken into account when creating a dictionary of abstract vocabulary. While defining the degree of abstraction of a word, a psychosemantic enquiry of native speakers of Russian can be helpful. Results of such interrogation are described in this article.